2018
DOI: 10.1177/1744806918801224
|View full text |Cite
|
Sign up to set email alerts
|

ZLc002, a putative small-molecule inhibitor of nNOS interaction with NOS1AP, suppresses inflammatory nociception and chemotherapy-induced neuropathic pain and synergizes with paclitaxel to reduce tumor cell viability

Abstract: Elevated N-methyl-D-aspartate receptor activity contributes to central sensitization. Our laboratories and others recently reported that disrupting protein–protein interactions downstream of N-methyl-D-aspartate receptors suppresses pain. Specifically, disrupting binding between the enzyme neuronal nitric oxide synthase and either its upstream (postsynaptic density 95 kDa, PSD95) or downstream (e.g. nitric oxide synthase 1 adaptor protein, NOS1AP) protein partners suppressed inflammatory and/or neuropathic pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
(92 reference statements)
1
11
0
Order By: Relevance
“…on day 0, 2, 4, and 6 (approximately 48 hours between injections); cumulative dose 16 mg/kg) to produce a CIPN condition, as described previously. 14,19,21,42,[48][49][50]52,54,[83][84][85][86][87][88] Control mice received an equal volume of cremophor-based vehicle on the same treatment schedule. Development of paclitaxel-induced allodynia was assessed on day 0, 4, 7, 11, and 14.…”
Section: General Experimental Protocolmentioning
confidence: 99%
“…on day 0, 2, 4, and 6 (approximately 48 hours between injections); cumulative dose 16 mg/kg) to produce a CIPN condition, as described previously. 14,19,21,42,[48][49][50]52,54,[83][84][85][86][87][88] Control mice received an equal volume of cremophor-based vehicle on the same treatment schedule. Development of paclitaxel-induced allodynia was assessed on day 0, 4, 7, 11, and 14.…”
Section: General Experimental Protocolmentioning
confidence: 99%
“…The actions observed in mice treated with ZL006 in our study have paved the way for future dose optimization in preclinical trials and subsequent clinical trials. Besides, we also inspired other studies that employ similar agents targeting the PSD95/nNOS or its downstream node in the pathway, including IC87201 or ZLc002 (Florio et al 2009 ; Lee et al 2018 ; Lee et al 2015 ; Zhu et al 2014 ).…”
Section: Discussionmentioning
confidence: 90%
“…Also, stroke, neuropathic pain and early‐stage Alzheimer's disease are associated with the co‐morbid anxiety (Bierman, Comijs, Jonker, Scheltens, & Beekman, 2009; Campbell Burton et al, 2013; Knapp et al, 2017; Kwak, Yang, & Koo, 2017; Nicholson & Verma, 2004). Reportedly, nNOS–CAPON association mediates amyloid‐β‐induced neurotoxicity (Zhang et al, 2018), ischaemia‐induced impairment of structural plasticity (Ni et al, 2018) and inflammatory nociception and chemotherapy‐induced neuropathic pain (Lee, Carey, et al, 2018; Lee, Li, et al, 2018). We previously reported that dissociation of nNOS with CAPON by ZLc‐002 produces rapid onset of anxiolytic‐like effect (Zhu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%